Constitutional supervision - Gonzales Ojeda, Magdiel (2021)
The modern state, which basically identified as social and democratic state of law, part of the experience of that society, pass all or part of their self-regulatory mechanisms is left to the pure irrationality, and that only state action made possible by the development of administrative, economic, technical, programming, decisions, etc., can neutralize the dysfunctional effects of an uncontrolled economic and social development. Therefore, the State cannot be limited to ensure the environmental conditions of an alleged inherent social order, not to monitor the unrest in a self-regulating mechanism, but, on the contrary, must be the key regulator of the social system and must be available to the task of structuring society through direct or indirect measures. That is, the state cannot remain a simple traffic policeman, but become real and effective regulator or social policy, economic structure and the political and legal system of the country. The modern state, according to its political formula must ensure that the economic structure and the legal and political system to suit the requirements of the majority, so as to protect the state system. It is the social interests constitute a real expression of the will of the nation and democracy work not only in the social and political, but also economic.